Gene therapy of cardiac failure - Qadir, MI; Munir, I; Nisa, TU (Journal of College of Medical Sciences-Nepal, 2012)
Every year in the world there is increasing death rates due to heart failure. So it is very essential to cure the heart failure on a long term basis. For this purpose, gene therapy is somehow the best way. We can do this by discovering new pharmacological targets, producing regenerative medicine by use of stem cells, using adipose tissues for cardiac repair, using resynchronization therapy by changing the gene expressions, by correcting the gene expression of connexin43, by enhancing the mitochondrial function, insertion of ACE gene, curing the down regulation of calcium signaling protein, use of micro RNAs, modification of cardiovascular ion channels by gene therapy, silencing the myotrophin gene. Heart failure means the loss of heart functions; heart stops its working which may lead to death. Now a day, heart failure is dominating in the world. There are lots of factors involve in this disease. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 69-75 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6732